Biodistribution of Intra-Arterial and Intravenous Delivery of Human Umbilical Cord Mesenchymal Stem Cell-Derived Extracellular Vesicles in a Rat Model to Guide Delivery Strategies for Diabetes Therapies - Junfeng Li; Hirotake Komatsu; Erasmus K. Poku; Tove Olafsen; Kelly X. Huang; Lina A. Huang; Junie Chea; Nicole Bowles; Betty Chang; Jeffrey Rawson; Jiangling Peng; Anna M. Wu; et al. (MDPI AG, 2022)
Umbilical cord mesenchymal stem cell-derived extracellular vesicles (UC-MSC-EVs) have become an emerging strategy for treating various autoimmune and metabolic disorders, particularly diabetes. Delivery of UC-MSC-EVs is essential to ensure optimal efficacy of UC-MSC-EVs. To develop safe and superior EVs-based delivery strategies, we explored nuclear techniques including positron emission tomography (PET) to evaluate the delivery of UC-MSC-EVs in vivo. In this study, human UC-MSC-EVs were first successfully tagged with I-124 to permit PET determination. Intravenous (I.V.) and intra-arterial (I.A.) administration routes of [124I]I-UC-MSC-EVs were compared and evaluated by in vivo PET-CT imaging and ex vivo biodistribution in a non-diabetic Lewis (LEW) rat model. For I.A. administration, [124I]I-UC-MSC-EVs were directly infused into the pancreatic parenchyma via the celiac artery. PET imaging revealed that the predominant uptake occurred in the liver for both injection routes, and further imaging characterized clearance patterns of [124I]I-UC-MSC-EVs. For biodistribution, the uptake (%ID/gram) in the spleen was significantly higher for I.V. administration compared to I.A. administration (1.95 ± 0.03 and 0.43 ± 0.07, respectively). Importantly, the pancreas displayed similar uptake levels between the two modalities (0.20 ± 0.06 for I.V. and 0.24 ± 0.03 for I.A.). Therefore, our initial data revealed that both routes had similar delivery efficiency for [124I]I-UC-MSC-EVs except in the spleen and liver, considering that higher spleen uptake could enhance immunomodulatory application of UC-MSC-EVs. These findings could guide the development of safe and efficacious delivery strategies for UC-MSC-EVs in diabetes therapies, in which a minimally invasive I.V. approach would serve as a better delivery strategy. Further confirmation studies are ongoing.